2019
DOI: 10.2147/ott.s175176
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA SNHG16 induces sorafenib resistance in hepatocellular carcinoma cells through sponging miR-140-5p

Abstract: BackgroundSorafenib is widely used for treatment of hepatocellular carcinoma (HCC), but the acquired resistance remains a major obstacle for its application. Thus it is of critical importance to elucidate the molecular mechanisms underlying sorafenib resistance in HCC. This study aimed to determine the roles of long noncoding RNA SNHG16 in sorafenib-resistant HCC cells.MethodsHCC and matched adjacent normal liver tissue samples were obtained from 103 HCC patients. Sorafenib-resistant HepG2/SOR cell line was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 19 publications
0
39
0
Order By: Relevance
“…Research conducted by Cao et al indicated that SNHG16 was a poor prognostic marker, which can promote tumor proliferation by epigenetically silencing p21 in bladder cancer [10]. Meanwhile, SNHG16 contributes to sorafenib resistance by sponging miR-140-5p in hepatocellular carcinoma [17]. Christensen et al found that SNHG16 was upregulated in colorectal cancer by affecting lipid metabolism [9].…”
Section: Publication Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Research conducted by Cao et al indicated that SNHG16 was a poor prognostic marker, which can promote tumor proliferation by epigenetically silencing p21 in bladder cancer [10]. Meanwhile, SNHG16 contributes to sorafenib resistance by sponging miR-140-5p in hepatocellular carcinoma [17]. Christensen et al found that SNHG16 was upregulated in colorectal cancer by affecting lipid metabolism [9].…”
Section: Publication Biasmentioning
confidence: 99%
“…Some studies have revealed that upregulated SNHG16 expression predicted poor prognosis for some cancers [26]. Moreover, the expression level of SNHG16 is closely related to TNM stage, distant metastasis, lymph node metastasis, overall survival (OS), and other clinical attributes [17]. Therefore, we conducted a meta-analysis to investigate whether the lncRNA SNHG16 can be used as a prognostic biomarker for human cancers.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of SNHG16 is also remarkably upregulated in HCC cell lines. 15,[18][19][20][21][22][23] Further analysis showed that high expression of SNHG16 is associated with high tumor grade, multiple tumors, macrovascular invasion, large tumor size, and lymph node status, as well as poor diseasefree survival and shorter overall survival. 15,[19][20][21]23 In HCC patients, multivariate analysis identified SNHG16 overexpression as a significant independent predictor of poor prognosis.…”
Section: Overexpression Of Snhg16 and Clinical Significance In Cancermentioning
confidence: 99%
“…Ye et al and Guo et al both found that knocking down SNHG16 increased sensitivity to sorafenib in HCC cells via acting as an endogenous sponge for miR-140-5p, which indicates that SNHG16 might be a promising therapeutic target to boost the effectiveness of chemotherapy for HCC patients. 18,23 Osteosarcoma is a rare cancerous bone tumor characterized by high metastasis, rapid progression, and poor prognosis. 67 In the past few decades, there has been great progress in the diagnosis and treatment of osteosarcoma, but the OS is still unsatisfactory.…”
Section: Chemoresistance and Vasculogenic Mimicrymentioning
confidence: 99%
See 1 more Smart Citation